2017
DOI: 10.18203/2320-6012.ijrms20172433
|View full text |Cite
|
Sign up to set email alerts
|

Dengue infection in central India: a 5 years study at a tertiary care hospital

Abstract: Background: Dengue is one of the most important mosquito borne viral disease with wide spectrum of clinical presentation and often with unpredictable clinical evolution and outcome. Approximately 50 million infections occur annually world-wide, but what’s the real size of the problem in India?  Nobody truly knows...!!  Present study was carried out to determine seropositivity, clinical profile and seasonal variation of dengue infection in central India.Methods: Study was carried out from January 2012 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 12 publications
3
11
1
Order By: Relevance
“…This was comparable to the study, done by Deshkar et al 11 It is believed to be due to the intrinsically more permeable vascular endothelium and comparatively lower immunity in children rendering them more susceptible to dengue infections. 12 However, in the study conducted by Neerja M et al, high numbers of cases were seen in the adult age group.…”
Section: Age Group-wise Distributionsupporting
confidence: 90%
See 1 more Smart Citation
“…This was comparable to the study, done by Deshkar et al 11 It is believed to be due to the intrinsically more permeable vascular endothelium and comparatively lower immunity in children rendering them more susceptible to dengue infections. 12 However, in the study conducted by Neerja M et al, high numbers of cases were seen in the adult age group.…”
Section: Age Group-wise Distributionsupporting
confidence: 90%
“…Gunasekaran P et al 14 and Deshkar ST et al 11 have shown similar trends of positivity in their respective studies.…”
Section: Seasonal Variationmentioning
confidence: 59%
“…With an increase in morbidity, mortality rates, and economic burden, understanding of dengue infection is essential to assist policymakers and public health managers to prepare for and control outbreaks with limited resources for both diagnosis and treatment. 2 Dengue was earlier considered as an urban and semiurban disease but in recent years, dengue has become endemic in rural areas of India as well due to water storage practices and large-scale development activities in rural areas. This has increased the scale of the dengue challenge in the country.…”
Section: Discussionmentioning
confidence: 99%
“…1 Dengue virus is a positive-stranded RNA virus in the genus Flavivirus, family Flaviviridae. 2 There are four antigenically related but distinct serotypes of the dengue virus: DENV-1, DENV-2, DENV-3, and DENV-4. 3 Dengue was reclassified by WHO IN 2009 according to levels of severity as dengue without warning signs, dengue with warning signs like abdominal pain, persistent vomiting, fluid accumulation, mucosal bleeding, lethargy, liver enlargement, increasing hematocrit with decreasing platelets, and severe dengue which included dengue with severe plasma leakage, severe bleeding, or organ failure.…”
Section: Introductionmentioning
confidence: 99%
“…Similar study by Smita T et al, also showed higher percentage of male cases than females with a ratio of 1.55:1. 5 Coinfection cases were analysed separately and it showed that only 1.5% of the total cases were positive for dengue and malaria co-infection. Even though there is no clear pattern in the monthly distribution of co-infection cases, out of 5 total cases 3 were during the time of monsoon.…”
Section: Discussionmentioning
confidence: 99%